EFFICIENCY OF DIFFERENT FUNGICIDES AGAINST LEAF SPOT DISEASE OF GINGER - S. BANDYOPADHYAY; B. RAI; A. DEBNATH (The Bioscan, 2015)
Leaf spot of ginger caused by Phyllosticta zingiberi has become a serious phytopathological constraint now in cultivation in the ginger growing areas of India. Among the different fungicides and fungicides combination tested including control for management of Phyllosticta leaf spot disease of ginger, Hexaconazole (0.1%) first at disease appearance and then 2 times at 20 days interval produced the lowest leaf spot disease severity (PDI 12.12) followed by spray with 0.1% Propiconazole (PDI 12.95) and spray with mixture of Carbendazim and Mancozeb@ 0.1% first at disease appearance and then 2 times at 20 days interval (PDI 16.83). The highest yield of 6.42 kg/plot (12.94 t/ha) was obtained by 0.1% Propiconazole spray which is very closely followed by spraying with Hexaconazole @ 0.1% with a yield of 6.40 Kg/plot (12.90 t/ha). So, it can be concluded that spraying with Hexaconazole or Propiconzole @ 0.1% for 3 times is highly effective against leaf spot disease of ginger.